Nisbah Sinkronisasi Suplai N-Protein dan Energi dalam Rumen Sebagai Basis Formulasi Ransum Ternak Ruminansia - . Hermon; . Suryahadi; K G Wiryawan; S Hardjosoewignjo (Faculty of Animal Science, Bogor Agricultural University, 2008)
The experiment was conducted to determine the optimum synchronization ratio of N-protein and fermented organic matter (OM) in the rumen for the purpose of ration formulation for ruminant animals, in order to improve efficiency of rumen microbial N synthesis and feed efficiency. Nylon bag technique was adopted to determine ruminal characteristic of protein and OM degradation of feedstuffs (forage and concentrate diet) for which the synchronized index of N-protein and fermented OM in the rumen might be determined. By randomized block design, twelve local cattle were arranged to four groups. Each group was fed three types of diet that was different in synchronization ratio of supplying N-protein and fermented OM in the rumen, namely 20 g N/kg OM (R20); 25 g N /kg OM (R25); and 30 g N /kg MO (R30). The diets had iso-energy and iso-protein contents and had the same synchronization index. The results showed that the type of diet had no effect (P>0.05) on intake and digestibility of nutrients, N retention, average daily gain (ADG), and feed efficiency. But R20 had better parameter values than those of R25 and R30. It might be concluded that the diet having a synchronization ratio of 20 g N/kg fermented OM in the rumen will generate more efficient protein synthesis of rumen microbes and feed efficiency. Key words: synchronization index, microbial protein synthesis, ruminal characteristic